A 12-item short form of the Knee injury and Osteoarthritis Outcome Score (KOOS-12): tests of reliability, validity and responsiveness. Issue 5 (May 2019) - Gandek, B.; Roos, E.M.; Franklin, P.D.; Ware, J.E.
Summary: Objective: To evaluate reliability, validity and responsiveness of KOOS-12, a 12-item short form of the 42-item Knee injury and Osteoarthritis Outcome Score (KOOS) that provides Pain, Function and Quality of Life (QOL) scale scores and a summary knee impact score. Design: Data from 1, 392 knee osteoarthritis (OA) patients from the FORCE-TJR research cohort who completed KOOS before and 6 and 12 months after total knee replacement (TKR) were analyzed. KOOS-12 includes a pain frequency item and three items measuring pain during increasingly difficult (sitting/lying, walking, stairs) activities; function items about standing, rising from sitting, getting in/out of a car, and twisting/pivoting; and the 4-item KOOS QOL scale. Percent computable scale scores, floor and ceiling effects, internal consistency reliability, validity (scale correlations, tests of known groups validity using one-way analysis of variance (ANOVA)) and responsiveness (effect sizes, standardized response means) were compared for the KOOS-12, full-length KOOS, KOOS-PS and KOOS, JR. Results: Internal consistency reliability was above 0.70 for all KOOS-12 scales and ≥0.90 for the KOOS-12 Summary score. Validity and responsiveness of KOOS-12 Pain, Function and QOL scales was satisfactory and reached similar conclusions as comparable full-length KOOS scales. The KOOS-12 Summary score was most responsive in discriminating between groups who differed in global ratings of post-TKR change in physical capabilities and had the highest effect sizes and standardized response means. Conclusions: KOOS-12 was a reliable and valid alternative to KOOS in TKR patients with moderate to severe OA and provided three domain-specific and summary knee impact scores with substantially reduced respondent burden.